Abandoning Vietnam : How America Left and South Vietnam Lost Its War - Willbanks, James H., 1947- (Book collections on Project MUSE., 2004)
"A mere two years after the last American combat troops departed, North Vietnamese tanks rolled into Saigon, overwhelming a poorly trained, disastrously led, and corrupt South Vietnamese military. But those two years provided Nixon with the "decent interval" he desperately needed to proclaim that "peace with honor" had been achieved. Willbanks digs beneath that illusion to reveal the real story of South Vietnam's fall."--Jacket.